Botryosphaeria and Related Taxa Causing Oak Canker in Southwestern Spain - SÁNCHEZ, M E; Venegas, J; Romero, M A; Phillips, A J L; TRAPERO, A (Plant Disease, 2003)
ABSTRACT Although root disease caused by Phytophthora cinnamomi is considered to be the most frequent and damaging disease associated with Quercus spp. decline in southwestern Spain, cankers commonly are observed on branches of declining Mediterranean Quercus spp. in this region. In surveys carried out in eight declining Quercus forests, strips of necrotic inner bark were common on diseased branches. Botryosphaeria stevensii, B. dothidea, and Diplodia sarmentorum consistently were isolated from these branches. Isolates of all three species caused cankers when inoculated onto excised Quercus branches. Inoculations on healthy branches in the field also induced canker development, but only B. stevensii caused lesions that girdled and killed the branches. The optimum temperature for in vitro growth of B. stevensii and B. dothidea was above 25°C, with slow growth at 35°C. In contrast, D. sarmentorum had an optimum temperature for growth of about 21°C, and did not grow at 35°C. The common occurrence and wide distribution of these pathogens, their association with cankers, and their ability to infect Quercus spp. suggest that they may contribute to the Quercus spp. decline in southwestern Spain.
doi: 10.1094/PDIS.2003.87.12.1515
Keywords: Botryosphaeria ribis; diplodia mutila; Fusicoccum aesculi; Otthia spi- raeae; Quercus ilex; Quercus suber

Micoflora asociada al alcornoque - MuÑoz LÓPEZ, C; COBOS SUÁREZ, P; MARTÍNEZ SAAVEDRA, G; SOLDEVILLA PUGA, C; DÍAZ LLORENTE, M (II Congreso Forestal Español, 1997)
This proyect intends both to reflect a synthesis of the results obtained in the study of the fungi related to Q. suber L., first in the Parque Natural de los Alcornocales (Cádiz), and then in other areas of Spain, and to highlight the rol of especific fungi detected in the group of all mycetes which are described in the same work
Keywords: Armillaria mellea; diplodia mutila; Hypoxylon mediterraneum; mycology flora; phytophthora cinnamomi; Quercus suber

Vegetative compatibility and pathogenicity of Diplodia mutila isolates on oak - Ragazzi, A. (European journal of forest pathology, 1997)
Forty isolates of Diplodia mutila, a dieback agent on oaks were characterized by their capacity to produce heterokaryons, by their vegetative compatibility, and by their pathogenicity tests on Quercus cerris. The forty isolates were collected from Quercus cerris, Quercus frainetto, Quercus ilex, Quercus pubescens, Quercus robur and Quercus suber in different regions in Italy. Three nit mutants (nit,, nit, and nit,) were identified with different nitrogen sources: sodium nitrite, sodium nitrate, uric acid, ammonium tartrate and hypoxanthine. O n the two nutrient media employed, a potato dextrose agar (PDA) medium with chlorate (PDC), and a minimal agar medium with chlorate (MMC), isolates obtained from Q. cerris Felded the greatest number of mutants: 254 on PDC (out of a total of 583) and 190 on MMC (out o a total of 440). Nine vegetative compatibility grou s (VCGs) were identified. There was a strong association between these VCGs and host species. Alfisolates tested except one from Q. cerris were pathogenic.
Keywords: diplodia mutila; disease (voyant); nit mutants; Pathogenicity; Quercus; vegetative compatibility

Dieback of cork oak (Quercus suber) in Catalonia (NE Spain) caused by Botryosphaeria stevensii - LUQUE, J; Girbal, J (European Journal of Forest Pathology, 1989)
Botryosphaeria stevensii Shoemaker (anamorph: Diplodia mutila Fr. apud Mont.) is reported as the cause of canker and dieback of cork oak (Quercus suber L.) in Catalonia (NE Spain). It also causes wilting of trees after cork is removed for industrial purposes. Symptomatology and details of morphology for both anamorph and teleomorph are given.
Keywords: Botryosphaeria stevensii; canker; Cork oak; dieback; diplodia mutila; morphology (PG); Symptoms